Effect of granulometric characteristics of the filtration medium in prefiltration systems for domestic use purposes in isolated rural communities - Tiago Poncio; Samuel Lunardi; Samara Terezinha Decezaro; Luis Guillermo Romero-Esquivel; Raphael Corrêa Medeiros; Lucas de Aguiar; Marcus Soares (Revista Brasileira de Ciências Ambientais)
Decentralized water treatment systems have limitations when raw water has high concentrations of impurities. This study evaluated the influence of different granulometric characteristics of the filter medium on the clogging in pre-filtration systems for domestic use in isolated rural communities, to minimize the impact of impurities in fresh raw water on final treatment. Three pre-filters, filled with filtration material with effective diameters of 0.20, 0.40, and 0.60 mm, and low uniformity coefficient (1.6), were operated continuously for 116 days. At a depth of 5–20 cm, 87, 57, and 41% of the total head loss were concentrated in the granulometries of 0.20, 0.40, and 0.60 mm effective diameters, respectively. Except for apparent color, no statistical difference was identified in water quality parameters between the different granulometries used in the study. The pre-filters showed an average turbidity removal efficiency of 65%. True and apparent colors presented an average removal of 32 and 39%, respectively. Total coliforms were found up to 15 cm deep in the filtration medium. Heterotrophic bacteria were observed throughout the depth of the filtration medium, with more than 1,000 bacterial colonies found. The use of filter media with a larger effective diameter can bring operational benefits, as it shows cleaning frequencies two to three times lower than filter media with smaller granulometry, besides presenting longer filtration runs, minimizing the impact of system operation errors by the owner.